COVID-19; THE NEED FOR INCREASED RECOGNITION OF CUTANEOUS MANIFESTATIONS - Odekunle, Ayomikun; Kafi, Opeyemi; Olaiya, Aarinola; Olatunji, Oladipo (African Journal of Infectious Diseases (AJID), 2023)
It has been over three years since the first case of covid-19 was discovered in Wuhan, China. Since then there have been a lot of discussions around symptoms and sequelae of covid-19 such as respiratory, cardiac, and neurology problems. However, not a lot of attention has been drawn to skin manifestations of this disease despite the fact that the prevalence of covid-19 associated skin lesions could be as high as 20% in some countries.